Two‐dimensional imaging in a lightweight portable MRI scanner without gradient coils. Issue 2 (25th March 2014) - Cooley, Clarissa Zimmerman; Stockmann, Jason P.; Armstrong, Brandon D.; Sarracanie, Mathieu; Lev, Michael H.; Rosen, Matthew S.; Wald, Lawrence L.
<x xml:space="preserve">Abstract</x> Purpose As the premiere modality for brain imaging, MRI could find wider applicability if lightweight, portable systems were available for siting in unconventional locations such as intensive care units, physician offices, surgical suites, ambulances, emergency rooms, sports facilities, or rural healthcare sites. Methods We construct and validate a truly portable (<100 kg) and silent proof‐of‐concept MRI scanner which replaces conventional gradient encoding with a rotating lightweight cryogen‐free, low‐field magnet. When rotated about the object, the inhomogeneous field pattern is used as a rotating spatial encoding magnetic field (rSEM) to create generalized projections which encode the iteratively reconstructed two‐dimensional (2D) image. Multiple receive channels are used to disambiguate the nonbijective encoding field. Results The system is validated with experimental images of 2D test phantoms. Similar to other nonlinear field encoding schemes, the spatial resolution is position dependent with blurring in the center, but is shown to be likely sufficient for many medical applications. Conclusion The presented MRI scanner demonstrates the potential for portability by simultaneously relaxing the magnet homogeneity criteria and eliminating the gradient coil. This new architecture and encoding scheme shows convincing proof of concept images that are expected to be further improved with refinement of the calibration and methodology. Magn Reson Med 73:872–883, 2015. © 2014 Wiley Periodicals, Inc.